2022
DOI: 10.3389/fmicb.2022.839465
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Functional Diversity of Epiphytic Bacterial and Fungal Communities on Marine Macrophytes in an Intertidal Zone

Abstract: Marine macrophytes (seagrasses and macroalgae) and their epiphytic microorganisms play an important role in the ecological and biochemical processes of coastal oceans. However, simultaneous comparative studies on the biodiversity and functions of epiphytic bacteria and fungi associated with marine macrophytes have not been conducted. In this study, high-throughput sequencing technology was used to describe the epiphytic bacterial and fungal communities of 11 common macroalgae and 2 seagrasses from an intertida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
1
9
0
2
Order By: Relevance
“…Our finding that microbial communities associated with both the substrate and surrounding seawater were distinct from kelp microbiomes aligns with observations from other studies on macroalgae (11,37). Many of the core ASVs associated with D. antarctica belong to groups previously known to have macroalgal associations, such as Granulosicoccus and Leucothrix (7,8,38). Further examination of core microbial functions associated with D. antarctica revealed enrichment of heterotrophic bacteria in all populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that microbial communities associated with both the substrate and surrounding seawater were distinct from kelp microbiomes aligns with observations from other studies on macroalgae (11,37). Many of the core ASVs associated with D. antarctica belong to groups previously known to have macroalgal associations, such as Granulosicoccus and Leucothrix (7,8,38). Further examination of core microbial functions associated with D. antarctica revealed enrichment of heterotrophic bacteria in all populations.…”
Section: Discussionmentioning
confidence: 99%
“…Kagami et al ( 2014 ) found that Chytridiomycota play an important role in water bodies as they mainly feed on dead aquatic plants, but are grazed upon by zooplankton (Kagami et al, 2014 ). Fungi that live in different habitats vary as they adapt to the different conditions, but all play important ecological roles (Bärlocher & Boddy, 2016 ; Chen et al, 2022 ; Raja et al, 2008 ). Meanwhile, many unclassified fungi were also found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the eluent was filtered in a sterile environment with a vacuum suction filter, and the epiphytic bacteria were collected onto a 0.22 μm filter membrane. Then, the membrane was put into a sample tube and stored at −80°C ( 62 ). Finally, the samples were placed on dry ice and sent to BioMarker Technologies (Beijing, China) for sequencing.…”
Section: Methodsmentioning
confidence: 99%